Bad luck or a common reality? Multiple exposures a nurse to potentially infectious material: a case report - Mateusz Bożejko; Karolina Olech (Nofer Institute of Occupational Medicine, 2024)
Presented is the case of a nurse who had 4 occupational exposures to potentially infectious material between December 2020 and June 2022. In 2 of the cases, the source patient was unknown, so pharmacological HIV post-exposure prophylaxis was implemented (in 1 of these cases, the nurse developed weakness and increased dyspeptic symptoms, necessitating a change in the antiretroviral medications used). During the interview collection, the nurse reported that multiple exposures to potentially infectious material are common in her work environment, but most of these are not reported. This is supported by the results of several studies devoted to the problem of non-reporting of occupational exposures by health care workers. However, there is significant discrepancy in the results of these studies, which may be due to different methods. The authors of this article believe that after 10 years since the entry into force of the regulation of the Minister of Health standardizing procedures for dealing with injuries caused by sharp instruments used in the provision of health care services, a serious problem remains of non-reporting of cases by employees (resulting in a lack of post-exposure prophylaxis). The authors call for the introduction of a nationwide reporting system. There is also a need to increase the importance of prophylaxis of stabbings and to improve the quality of training of medical personnel in post-exposure prophylaxis procedures. Med Pr Work Health Saf. 2024;75(2):173-179